(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Pregnancy involves dynamic hormonal adjustments essential for maternal health and fetal development. Among these, Follicle-Stimulating Hormone (FSH), Luteinizing Hormone (LH), and Thyroid-Stimulating Hormone (TSH) play crucial roles in regulating reproductive and metabolic functions. Understanding their interrelationship provides insight into the physiological balance maintained during gestation. Objective: To review and analyze existing literature on the interrelationships between FSH, LH, and TSH in pregnant women, emphasizing physiological regulation, trimester-wise variations, and hormonal feedback mechanisms. Main Body: This study was conducted as a systematic literature review using databases including PubMed, ScienceDirect, Google Scholar, and Scopus. Studies published between 2020 and 2024 focusing on FSH, LH, and TSH variations in pregnancy were identified and reviewed. Relevant data were extracted, compared, and thematically analyzed. The review revealed that FSH and LH levels are markedly suppressed during pregnancy due to high estrogen, progesterone, and placental hormone activity, while TSH levels fluctuate depending on maternal thyroid status and gestational age. Several studies indicate a subtle but significant hormonal interdependence between thyroid function and gonadotropin regulation. However, regional data and combined hormone analyses remain limited. Conclusion: The interaction between FSH, LH, and TSH reflects the complex endocrine coordination required for maintaining a healthy pregnancy. Further population-based research is needed to establish reference values and clarify these hormonal relationships to improve early detection and management of endocrine disturbances in pregnant women.